Carbon Deposition and Sulfur Tolerant La0.4Sr0.5Ba0.1TiO3–La0.4Ce0.6O1.8 Anode Catalysts for Solid Oxide Fuel Cells. (1st January 2015) - Sun, Yi-Fei; Li, Jian-Hui; Cui, Shao-Hua; Chuang, Karl T.; Luo, Jing-Li
Highlights: Carbon deposition and sulfur tolerant perovskite LSBT–LDC anode was prepared. LSBT–LDC showed higher electrochemical performance than LSBT anode in sour CH4 . The addition of LDC contributed to the removal of carbon deposition on anode. Abstract: In this work, LSBT–LDC (La0.4 Sr0.5 Ba0.1 TiO3 –La0.4 Ce0.6 O1.8 ) was successfully prepared by impregnating LSBT and LDC solutions on porous YSZ matrix. The prepared anode material exhibited higher catalytic performance and better resistance against carbon deposition than LSBT anode material in 5000 ppm H2 S containing methane. Electrochemical impedance spectra (EIS) characterizations revealed that the addition of LDC significantly reduces the activation polarization resistance. Energy-dispersive X-ray spectroscopy (EDX) results indicated that the distribution of impregnated oxides in the matrix was uniform. The results of X-ray photoelectron spectroscopy (XPS) and temperature-programed oxidation (TPO) indicated that LSBT–LDC anode could enhance the tolerance against carbon deposition. The gas chromatography (GC) analysis proved that the modification of LDC could effectively promote the activation of methane and contribute to remove carbon deposition formed on the catalyst simultaneously.